Role of Telemedicine in Pace of Consultation and Physicians’ Satisfaction in Thoracic Surgery ICU - Fadaizadeh, Lida (Tanaffos, 2018)
BACKGROUND: Despite various applications of tele-ICU, there are still many questions about its costs and advantages in ICU. Some of its advantages are accelerating consultations and bringing physicians’ satisfaction from tele-consultation outcomes. The aim of this study is to discuss these advantages. MATERIALS AND METHODS: Initially a telemedicine network was implemented and in the case of having no related specialist, the physicians used telemedicine network to perform specialized tele-consultation to thoracic surgery ICU patients. ICU patient’s documents during a year before tele-consultation were studied and delay time in consultation was recorded and compared between the two phases. Finally, the physicians’ satisfaction with tele-consultation was evaluated. RESULTS: Fifty-eight tele-consultations in various medical fields were carried out, of which 27 were neurology cases. From the time of receiving a consultation request to its performance, the mean time was 1.3 days in tele-consultation. Tele-consultations were given 2.5 times faster than face to face method. In evaluation of physicians’ satisfaction, 82.75% of them were fully satisfied from tele-consultation, 12.06% were partly satisfied and 5.17% were not satisfied. CONCLUSION: Since the length of hospitalization in ICU is crucial due to heavy costs of treatment, high risk of contamination and limited beds, performing timely consultation is a key factor in reducing hospitalization period. Tele-consultation in thoracic surgery ICU not only accelerates patient care, but also results in higher physician satisfaction.